2019
DOI: 10.1007/s40093-019-0287-1
|View full text |Cite
|
Sign up to set email alerts
|

Time-dependent release of some plant nutrients from different organic amendments in a laboratory study

Abstract: Purpose Soil fertility management requires a precise assessment of nutrient release from organic amendments to decide the rates and frequency of application. Methods Time-dependent release of some macro-and micro-nutrients from farmyard manure, mushroom compost, poultry manure, vermi-compost, biogas slurry and biochar of Lantana sp. was studied during 120 days incubation through entrapment of released nutrients on ion exchange resins. Results Highest total concentration of K, Ca, Mg and S was in farmyard manur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 22 publications
3
14
0
Order By: Relevance
“…Both studies attributed the slower release to desorption of Zn from inside macro‐ or micro‐aggregates, while Sadusky et al () described zero order nutrient release as a surface‐controlled process attributable to the weathered nature of soils. In a laboratory study to investigate time‐dependent release of Zn from biochar over the course of 120 d, Dey et al () observed a Zn accumulation throughout the period, which, although formally statistically non‐significant, conformed to zero order release kinetics. Hence, our observation of zero order kinetics in stage 2 indicates the release of zinc from the recalcitrant soil reservoir.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both studies attributed the slower release to desorption of Zn from inside macro‐ or micro‐aggregates, while Sadusky et al () described zero order nutrient release as a surface‐controlled process attributable to the weathered nature of soils. In a laboratory study to investigate time‐dependent release of Zn from biochar over the course of 120 d, Dey et al () observed a Zn accumulation throughout the period, which, although formally statistically non‐significant, conformed to zero order release kinetics. Hence, our observation of zero order kinetics in stage 2 indicates the release of zinc from the recalcitrant soil reservoir.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has investigated the potential of organic amendments as Zn fertilizers. Suitable potential sources include: sewage sludge ( Motaghian and Hosseinpur , ), green manures made from red clover and sunflower ( Aghili et al, ), poultry manure ( Ravindran et al, ), cow manure and vermicompost ( Motaghian and Hosseinpur , ), biogas slurry ( Malav et al, ; Dey et al, ), brewery waste sludge ( Ahmed et al, ), and seaweed ( Possinger , ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Manures have manifold benefits on the soil physical, chemical and biological characters 28 and have the ability to supply plant nutrient for two or more crop seasons. 29 Therefore, growth characteristics and seed yield of sesamum showed significant improvement due to residual effect of application of enriched compost @ 2.5 and 5.0 t/ha compared to non application of enriched compost.…”
Section: Lai Days To 50% Flowering and Yield Of Sesamum Fertility Managementmentioning
confidence: 90%
“…Evidently addition of various substrates of organic matter resulted in building up of DTPA-extractable micronutrients and HWS-B. all extractable micronutrients compared to soil with mineral fertilization which in turn, could influence the availability of micronutrients to plants (Dey et al, 2019). Farmers in the north-east have been applying various organic manures since time immemorial (Basumatary et al, 2000).…”
Section: Issn: 2319-7706 Volume 9 Number 8 (2020)mentioning
confidence: 99%